Barriers to inclusive education and support services for children with autism and developmental delays in Brazil - Minetto, Maria de Fátima Joaquim; Kruszielski, Leandro; Matos, Elyse Michaele Bacila Batista de; Choinski, André Marques (Frontiers in Education, 2026)
BackgroundBrazil, the largest South American nation, lacks comprehensive data on services for children with autism spectrum disorder (ASD) and other neurodevelopmental delays (NDD), such as cerebral palsy, speech impairments, and ADHD. While outdated regional studies estimate ASD prevalence at 27.2 per 10,000 children, global trends suggest rising rates. Limited research highlights barriers like delayed diagnosis, family stress, and access to health and social services, despite an increase in legal rights since 2012 (ASD Statute). This study uses a large community sample to characterize caregiver needs, acknowledging socioeconomic biases in the cohort.MethodsWe adapted and translated the Autism Speaks Family Needs Assessment (FNA) survey to Brazilian Portuguese following WHO guidelines. The Ico Project Foundation disseminated the online survey via social media networks (September–October 2020, amid the COVID-19 peak). No proof of diagnosis was required; 5,220 responses were collected, with 4,940 selected for analysis (descriptive statistics and logistic regression controlling for demographics).ResultsThe research revealed that 68.5% of children were diagnosed with Autism Spectrum Disorder (ASD) or developmental delays before the age of 3, with higher-income families and those from more developed regions of Brazil accessing diagnoses earlier. Furthermore, medical and educational attention were identified as the biggest challenges, and caregivers’ education level and family income were significantly associated with various difficulties and care priorities.DiscussionDespite the privileged socioeconomic profile of the sample, systemic gaps and unmet needs persist, with notable disparities in access to services based on income and geographical location, reinforcing the urgency of policies for equitable diagnoses, clinical interventions, and inclusive education in Brazil.